Field orientation based three‐coil decoupled wireless transmitter for electric vehicle charging with large lateral receiver misalignment tolerance. Issue 5 (28th January 2021) - Nie, Shuang; Pathmanathan, Mehanathan; Yakop, Netan; Luo, Zhichao; Lehn, Peter W.
Abstract: A three‐coil decoupled transmitter is developed for the inductive power transfer system of electric vehicle charging. The three‐coil decoupled transmitter consists of three overlapping rectangular coils with magnetic mutual decoupling and is capable of overcoming large receiver lateral misalignment up to 20 cm. A current optimization method is advanced to derive transmitter coil currents for the multi‐phase system that minimizes the coil loss through optimizing the current distribution among transmitter coils. The optimized current distribution reduces the maximum leakage flux by around 40% compared to the best alternative excitation method. The compensation strategy provides unity power factor for high‐power transfer phases and allows a single set of compensation capacitors to be used regardless of receiver alignment. The three‐coil decoupled transmitter is compatible with a typical three‐phase inverter for industrial practical application, which halves the power electronic switches used with previous topologies. The simulation verification is performed at 3.3 kW, achieving 93.76% efficiency at perfect alignment and 92.54% efficiency at 20 cm misalignment. The experimental verification is implemented at 3.3 kW with 200 mm ground clearance, realizing a 92.97% efficiency at perfect alignment and 90.57% efficiency at 20 cm misalignment.